AODTH-007 Dietary manipulation of the healthy human and colitic rat gut microbiome by cd-treat diet and exclusive enteral nutrition; a proof of concept study. (17th June 2017) - Svolos, V; Hansen, R; Ijaz, UZ; Quince, C; Watson, D; Alghamdi, A; Brejnrod, A; Ansalone, C; Klopfleisch, R; Milling, S; Gaya, DR; Russell, RK; et al.
Abstract : Introduction: The extensive modulation of the gut microbiome in Crohn's disease (CD) children treated with exclusive enteral nutrition (EEN) offers clues about EEN's potential mode of action; but also on the development of novel therapies through dietary manipulation of the gut microbiota. This proof of concept study compared the effect of a novel 'ordinary' food diet (CD-TREAT diet) and EEN on A)healthy human and B)colitic rat gut microbiota. Method: A)Healthy adults followed two experimental diets for 7 days with a 15 day wash out period in between; EEN and CD-TREAT, an "ordinary" food diet with similar nutrient and food ingredient composition to EEN. Faecal and urine samples were collected before and after each intervention and 16srRNA sequencing, untargeted faecal and urine metabolomics were performed; B)10-month-old HLA-B27 and HLA-B7 trangenic rats received EEN, CD-TREAT or regular rat chow for 4 weeks. Faeces were collected before, during and post treatment and gut contents/tissue at sacrifice. Disease activity was quantified by blinded histological scores. Gut bacterial metabolic activity was measured by faecal short chain fatty acids (SCFA) quantification. Results: A)100 faecal and urine samples were collected from 25 healthy adults. Gut bacterial community structure significantly changed after both EEN (R2=0.15, p=0.001) and CD-TREAT (R2=0.05, p=0.003) and shifted towards the same direction. EEN's and CD-TREAT's impact on 3%OTU community structures was strongly correlated (R2=0.38, p<2.2e-16). Untargeted faecal metabolomics also revealed a strong correlation between the EEN and CD-TREAT changes (R=0.31, p<10^−14); B)100 faecal samples were collected from 12 HLA-B27 and 8 HLA-B7 transgenic adult rats. Both dietary interventions increased the body weight of the HLA-B27 rats (Median%change, EEN:+9, CD-TREAT:+16, Control:−2) and decreased the weight of caecum and colon contents. Faecal concentration of total SCFA, acetic and propionate decreased while isobutyric and isocaproic increased during both diets. Histopathology scores revealed that both diets benefited moderately ileal but not colonic inflammation. Conclusion: We have developed an "EEN composition-like" food diet which induces similar gut microbiome changes with EEN. These proof of concept data support a subsequent pilot trial in patients with active CD. Disclosure of Interest: None Declared